Kekuatan Hukum Surat Assesment BNNP Sebagai Rekomendasi Bagi Hakim Untuk Memutus Pelaksanaan Rehabilitasi Terhadap Penyalaguna Narkotika di Kota Jambi - Putri, Septia Intan; Sahabuddin, S; Nggeboe, Ferdricka (Legalitas: Jurnal Hukum, 2024)
It is known that the assessment is an assessment action to determine the resident's condition due to drug abuse which includes medical and social aspects. The assessment is carried out by means of interviews, observations and physical and mental examination of the suspect by investigators. So that investigators can determine whether the suspect has the right to receive an assessment application. However, even though narcotics abusers have received an assessment letter to undergo rehabilitation, several drug abusers have not had their assessment applications approved by the judge. The purpose of writing is to find out and analyze the legal strength of the BNNP assessment letter as a recommendation for judges to decide on the implementation of rehabilitation for narcotics abusers in Jambi City. In this research the author uses an empirical juridical research method, namely "research in the form of field studies starting from primary data to find theories regarding the process of occurrence and the process of how the law works. Meanwhile, the empirical approach (law as social, cultural or das sein reality), because in this research primary data obtained from the field is used. Data obtained from interviews and direct observation